Antibacterial property of moringa oleifera seed extract: comparative study of crude extract and membrane processed extract - Idris Oseni, Munirat; Jami, Mohammed Saedi; Abdul Karim, Mohamed Ismail; Jamal, Parveen; Muyibi, Suleyman Aremu (Journal of Pure and Applied Microbiology, 2014)
In this research, the antibacterial property of both crude and membrane processed seed extracts were investigated against Escherichia coli, Pseudosomonas aeruginosa Bacillus subtilis and Staphylococcus aureus. The defatted seeds were prepared with water and the water extract obtained was passed through 0.45?m microfiltration membrane system. The antibacterial activity was done using the agar well diffusion. The effect of concentration of the extracts were determined, the Minimum Inhibitory Concentration (MIC) as well as Minimum Bactericidal Concentration (MBC) was carried out. The result showed that the diameter inhibition zone ranges from 13mm to 30mm and increase in the seed extracts showed a corresponding increase in the inhibition of the bacterial strains. Statistical difference was found (P = 0.002) when the mean of antibacterial activity of the membrane processed seed extract against the bacterial strains was compared with the crude seed extract. Statistical results showed that membrane processed extract was more effective than the crude extract. The results of MIC and MBC values of membrane processed extract seed obtained shows that it was bactericidal against Pseudosomonas aeruginosa, Bacillus subtilis, and bacteriostatic against Escherichia coli Staphylococcus aureus respectively.